A genetic linkage map of guinea yam (Dioscorea rotundata Poir.) based on AFLP markers - Mignouna, H.; Mank, R.; Ellis, T.; Bosch, N. van den; Asiedu, Robert; Ng, S.; Peleman, J. (Springer, 2002)
A genetic linkage map of the tetraploid white yam (Dioscorea rotundata Poir.) was constructed based on 341 co-dominantly scored amplified fragment length polymorphism (AFLP) markers segregating in an intraspecific F1 cross. The F1 mapping population was produced by crossing a landrace cultivar TDr 93-1 as female parent to a breeding line TDr 87/00211 as the male parent. The marker segregation data were split into maternal and paternal data sets, and separate genetic linkage maps were constructed since the mapping population was an F1 cross between two presumed heterozygous parents. The markers segregated like a diploid cross-pollinator population suggesting that the D. rotundata genome is an allo-tetraploid (2n = 4x = 40). The maternal map comprised 155 markers mapped on 12 linkage groups with a total map length of 891 cM. Three linkage groups consisted of maternal parent markers only. The paternal map consisted of 157 markers mapped on 13 linkage groups with a total map length of 852 cM. Three and one quantitative trait loci (QTLs) with effects on resistance to Yam Mosaic Virus (YMV) were identified on the maternal and paternal linkage maps, respectively. Prospects for detecting more QTLs and using marker-assisted selection in white yam breeding appear good, but this is subject to the identification of additional molecular markers to cover more of the genome.